Changes in the tryptophan-kynurenine axis in association to therapeutic response in clinically depressed patients undergoing psychiatric rehabilitation. (August 2018) - Reininghaus, B.; Riedrich, K.; Dalkner, N.; Bengesser, S.A.; Birner, A.; Platzer, M.; Hamm, C.; Gostner, J.M.; Fuchs, D.; Reininghaus, E.Z.
Highlights: Depressed individuals undergoing a six-week psychiatric rehabilitation were included. Changes in Trp, Kyn and the Kyn/Trp-ratio as well as hsCRP and IL-6 were measured over time. Comparisons between treatment responders and non-responders were made. A significant group x time interaction for Kyn and Kyn/Trp was found. Changes in Kyn and hsCRP correlated with changes in BMI over time. Abstract: Introduction: In recent decades a number of studies have shown an association between the Tryptophan (Trp)-Kynurenine (Kyn) axis and neuropsychiatric disorders. However, the role of the Trp-Kyn pathway on the affective status in a general psychiatric cohort requires clarification. This study aimed to measure peripheral changes in Trp, Kyn and the Kyn/Trp-ratio as well as in the inflammatory markers high sensitive C-reactive protein (hsCRP) and interleukine-6 (IL-6) in individuals undergoing a six-week course of intensive treatment program comparing subgroups of treatment responders and non-responders. Methods: In this investigation 87 currently depressed individuals with a life-time history of depressive disorders were divided into treatment responders (n = 48) and non-responders (n = 39). The individuals were selected for an extreme group comparison out of 598 patients undergoing a 6-week psychiatric rehabilitation program in Austria. Responders were defined according to great changes in Becks Depression Inventory (BDI-II) between time of admission and discharge (BDI-II > 29 to BDI-II <14), while non-responders had no or minimal changes (BDI >20, max. 4 points change over time). Differences in the levels of Trp, Kyn, and the Kyn/Trp ratio as well as levels of hsCRP and IL-6, were compared between groups. Differences were analyzed at the time of admission as well as at discharge. Results: A significant group x time interaction was found for Kyn [ F(1.82) = 5.79; p = 0.018] and the Kyn/Trp ratio [ F(1.85) = 4.01, p = 0.048]. Importantly, Kyn increased significantly in the non-responder group, while the Kyn/Trp ratio decreased significantly in the responder group over time. Furthermore, changes in Kyn as well as hsCRP levels correlated significantly with changes in the body mass index over time (Kyn: r =0.24, p = 0.030; hsCRP: r =0.25, p = 0.021). No significant interactions were found for Trp and hsCRP, although they increased significantly over time. Discussion: Given the limitations of the study, we could show that the therapeutic response to a multimodal treatment in clinically depressed patients not receiving cytokine treatment is associated with changes in Kyn levels and the Kyn/Trp ratio as well as with hsCRP. However, it is too early to draw any causal conclusion. Future research should clarify relevant clinical and neurobiological parameters associated with changes in Kyn levels and Kyn/Trp ratio, especially in regard to clinical response.